ANTIDIABETIC ACTIVITY OF THE COMBINATION OF SEPAT RAWA FISH FLOUR (Trichopodus thricopterus) AND ETHANOL EXTRACT OF RAMANIA LEAVES (Bouea Macrophylla Griffith): AKTIVITAS ANTIDIABETES KOMBINASI TEPUNG IKAN SEPAT RAWA (Trichopodus thricopterus) DAN EKSTRAK ETANOL DAUN RAMANIA (Bouea Macrophylla Griffith) - Fitriyanti; Ika Astuti, Karunita (SPIN JURNAL KIMIA & PENDIDIKAN KIMIA, 2024)
Diabetes mellitus is a metabolic disease with impaired insulin secretion. Sepat Rawa fish has been proven to contain alpha-amino acids, which can increase insulin action by increasing energy in the cell metabolic cycle. Ramania leaves contain compounds for antidiabetic treatment, such as saponins and flavonoids. This study aims to find the best dose to increase the antidiabetic activity of the combination of sepat rawa fish meal and ethanol extract of ramania leaves. This research activity uses pre- and post-tests with a control group design. The 25 mice used were divided into 5 groups, namely group I: negative control (CMC Na 0.5%), group II: positive control (glibenclamide 3 mg/kgBW), group III: sepat Rawa fish meal dose of 300 mg/kg. KgBW, group IV: ramania leaf extract at a dose of 300 mg/kg BW, group V: a combination of fish meal 300 mg/KgBW and ethanol extract of ramania leaf 300mg/kg BW. Mice were induced by alloxan to experience hyperglycemia. Observations on the decrease in blood sugar levels of each test group were carried out on the 7th day after alloxan induction by taking sufficient blood from the tails of mice and measuring using glucose. Data was analyzed for variance (ANOVA) (p=0.05). The result is that a single group of Ramania extract with a dose of 300 mg/KgBB shows the best activity with a percent decrease in blood sugar levels by 28.438,  a combination dose of 25.107 %, and a Sepat Rawa dose of 21,675%. The Third of them was not significantly different with positive control.